Value innovation activities in the wireless telecommunications service sector: A case study of the Malaysian market - Hajar, Mohamed A.; Daing Nasir, Ibrahim; Mohd Ridzuan, Darun; Al-Sharafi, Mohammed A. (Scholar Commons, 2020)
Innovation has become an important source of growth and survival for the telecom industry, especially with the highly competitive, dynamic business environment of this sector. The telecom market attributes of liberalization, privatization and globalization result in fierce competition, which aggravates telecom firms’ challenges to expand their market share, and hence, increase customer base, sales volume, and ultimately profit. A new strategy to succeed is innovation differentiation, which leads to breaking out the competition and creating uncongested market space. The aim of this paper is to highlight the logic of value innovation in the wireless telecom sector. A qualitative research approach was used to analyze the actions related to value innovation in the mobile service sector in Malaysia. In particular, this study focuses on the motivation, and hence the changed strategies, of telecom service providers to embrace value competition rather than traditional tariff competition in order to enhance customer satisfaction and encourage customer loyalty, which will ultimately result in higher profitability and growth. The services and loyalty packages provided by the telecom firms were reviewed through employing analytical case study. Also, this paper highlights the drawbacks and limitations of the services that did not live up to the expectations of customers and failed to earn their loyalty. Moreover, this study gives suggestions to service providers regarding ways to achieve long-run profitable growth.